Increasing the impact strength and wear resistance of Hadfield steel used in excavator teeth and crusher hammers by adding chromium and molybdenum - ضاهر نسيم; علي هترة; احمد سلامة (Latakia University Journal -Engineering Sciences Series, 2024)
Work has been done on adding chromium and molybdenum to Hadfield steel, from which crusher hammers and excavator teeth are made. The process of smelting the metals required to form Hadfield steel with chromium and molybdenum in different proportions was carried out according to two meltings, then casting the samples in sand molds and performing rapid cooling in water after casting, then testing the impact, wear and hardness of the samples. The results showed an increase in hardness and thus an increase in wear resistance. The impact toughness also increased as a result of the addition of chromium and molybdenum. Thus, the resulting steel became more tolerant of heavy service conditions, which leads to economic cost savings in addition to the scientific aspect..